Cytomegalovirus induced hemophagocytic lymphocytic histiocytosis in two pediatric patients with acute lymphoblastic leukemia. (2017) - Waddell, Benjamin; Razzouk, Bassem; Willey, Emily; Belcher, Chris
Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a rare inflammatory condition with tissue destruction due to abnormal immune activation. We present a series of 2 cases of cytomegalovirus-induced HLH in children during maintenance chemotherapy for acute lymphoblastic leukemia. These cases emphasize the importance of considering secondary HLH in this high-risk subset of pediatric patients.